Factors Correlated with the Accuracy of Colposcopy-Directed Biopsy: A Systematic Review and Meta-Analysis. Issue 2 (1st February 2022) - Ren, Hongyan; Jia, Mengzhe; Zhao, Shujun; Li, Hongyu; Fan, Suzhen
Abstract: Purpose/aim of the study: Colposcopy-directed cervical biopsy has played a major role in diagnosing cervical lesions. The precision of colposcopy-guided biopsy has been questioned. We analyzed several factors that may be correlated with the accuracy of biopsy. Methods: PubMed, EMBASE were searched from January 1, 1998 to March 1, 2020. Odds ratio with 95% confidence intervals (CIs) were calculated. Selection criteria: Included studies evaluated factors correlated with the accuracy of biopsy and patients' final diagnosis was established by histological examination of the specimen obtained by conization, loop electrosurgical excision procedure (LEEP), or colpohysterectomy. Results: A total of 10 studies were selected for the systematic review and meta-analysis. The pooled analysis indicated that the diagnostic inaccuracies of colposcopy-directed cervical biopsy were magnified in women who were 50 years of age or older. Postmenopausal status and transformation zone 3 type were also associated with the diagnostic inaccuracies of colposcopy-directed biopsy. High-grade squamous intraepithelial lesions had better concordance rates than low-grade squamous intraepithelial lesions. The number of vaginal deliveries, number of biopsies, and HPV type were associated with biopsy underdiagnosis and biopsy overestimation. Conclusions: This meta-analysis found that the correlation between the histological findings at biopsy and after surgical treatment was influenced by women's age, menopausal status, and the transformation zone type. The diagnostic efficacy was also better for high-grade squamous intraepithelial lesions than for low-grade squamous intraepithelial lesions. Further large-scale randomized clinical trials are required to analyze the factors correlated with biopsy underdiagnosis and biopsy overestimation.